Comprehensive characterization and health assessment of occupational exposures to volatile organic compounds (VOCs) in Xi'an, a major city of northwestern China. (1st February 2021) - Xu, Hongmei; Li, Yaqi; Feng, Rong; He, Kailai; Ho, Steven Sai Hang; Wang, Zexuan; Ho, Kin Fai; Sun, Jian; Chen, Jiawen; Wang, Yao; Liu, Ying; Wang, Feiyu; et al.
Abstract: The personal exposure to volatile organic compounds (VOCs) was determined in five occupational groups (including printing shop employees, office workers, furniture store employees, bus and taxi drivers) in the capital city of Xi'an in northwest China. The highest personal exposure concentration (258.7 ± 10.0 μg m −3 ) to the 64 Air Toxics VOCs classified by the United States Environmental Protection Agency (U.S.EPA), as well as associated health risk potential, were seen in the furniture store employees. These could be attributed to off-gassing from brand new furniture and volatiles from cleaning reagents. Aromatic species were the dominant class in the personal exposure samples collected from the groups of printing shop employees, office workers, and bus and taxi drivers, with the concentrations of 49.8–74.4 μg m −3 and mass compositions of 34.8–43.2% of the sum of the 64 Air Toxics for the cases studied. The highest personal exposure to carbonyls (C≥3 ) of 100.4 ± 25.6 μg m −3 and composition of 38.8% were again seen in the furniture store employees. The unique VOC composition profiles represented potential indoor or in-vehicle sources in each workplace. Moreover, environmental tobacco smoke (ETS) contributed to the personal exposure to many of the Air Toxics species, especially methyl butyl ketone and 1, 2-dibromoethane. The cancer risks of Class 1 carcinogens of vinyl chloride, 1, 3-butadiene, and benzene, were 1.4, 12, and 5.2 times, respectively, of the threshold of carcinogenicity (1 × 10 −6 ). Acrolein showed the highest non-cancer risk which was 150 times the acceptable level (1.0). The results could offer a scientific basis for the government to establish the occupational air quality standards to the toxic VOCs in China. Graphical abstract: Image 1 Highlights: Exposure to VOCs was studied in printing shop, office, furniture shop, bus and taxi. Acetone, ethanol, toluene, naphthalene, and acrolein were the most abundant VOCs. The highest exposures and health risks were both seen for furniture store employees. Environmental tobacco smoke showed contribution to the VOCs personal exposure. Cancer risks of Class 1 species and non-cancer risk of acrolein exceeded the limits.